High time resolution, two-dimensional position sensitive MSMGRPC for high energy physics experiments - Petriş, Mariana; Aprodu, V.; Bartoş, D.; Caragheorgheopol, A.; Dorobanţu, D.; Petrovici, M.; Prodan, L.; Radu, A.; Frühauf, J.; Deppner, Ingo Martin; Herrmann, Norbert (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2023)
Two Multi-Strip Multi-Gap Resistive Plate Counters (MSMGRPCs) designed to cope with the high counting rates and track densities of the most challenging zone of the CBM-TOF wall were successfully tested in-beam in the mCBM experimental setup installed at SIS18/GSI Darmstadt facility (FAIR Phase-0). At low counting rate a 96% efficiency plateau and 45 ps time resolution were obtained. The high counting rate test showed ∼50 ps time resolution and an efficiency ≥90% at the maximum delivered counting rate of 30 kHz/cm2. For the mitigation of the gas pollution aging effects, a new detector architecture with a direct gas flow through the gas gaps is proposed. The assembled prototype was tested in-beam in the mCBM setup, obtaining similar performances with the ones obtained for the prototypes with gas exchange via diffusion.